2009
DOI: 10.1007/s12149-009-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maximum standardized uptake value (SUVmax) of lung cancer and lymph node metastasis on FDG-PET

Abstract: The likelihood of lymph node metastasis increases with an increase of the SUV of a primary lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 17 publications
4
37
3
2
Order By: Relevance
“…These results further suggested that SUVmax may in partly reflect the potential of metastasis in primary tumor in NSCLC and are in line with other studies (Li et al, 2009;Nambu et al, 2009). However, there was no upper threshold of SUVmax of NSCLC, above which lymph node and/or distant organ metastasis were always present.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results further suggested that SUVmax may in partly reflect the potential of metastasis in primary tumor in NSCLC and are in line with other studies (Li et al, 2009;Nambu et al, 2009). However, there was no upper threshold of SUVmax of NSCLC, above which lymph node and/or distant organ metastasis were always present.…”
Section: Discussionsupporting
confidence: 92%
“…Metastasis is the major cause of death due to several malignancies, including NSCLC and it occur primary by dissemination through the lymphatic and blood vessels. Nambu et al (2009) have reported that the likelihood of lymph node metastasis increases with increase of SUVmax of the primary tumor in patients with NSCLC. Our results are consistent with their observations.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies concluded that the likelihood of lymph node metastasis increases with an increase in SUV max of the primary tumor (22,23). Our results are not consistent with those observations.…”
Section: Discussioncontrasting
confidence: 99%
“…La probabilitĂ© d'atteinte ganglionnaire ou de mĂ©tastases Ă  distance serait corrĂ©lĂ©e au SUVmax de la lĂ©sion primitive [33][34][35]. Celui-ci pourrait constituer un facteur pronostique au mĂȘme titre que la classification TNM lors du bilan d'extension initial du CBNPC.…”
Section: Discussionunclassified